Applying Some Elements of Just in Time System to Improve TELMEC’s Internal Production Performance - Gomes Eduardo, Adao Francisco (2009)
The author has been doing its Dissertation Project at Strategic Business unit (SBU), which is one of the TELMEC Company’s Factory Units, that produces mainly domestics cooking pots and pans. The factory has been presenting some internal production performance issues. One of these issues which have been affecting the production is the excessive transportation of material handling caused by old production layout design, and the inadequate co-ordination of information process causing an increase amount of inventory and internal congestions. In order to improve the production performance, is necessary to create capacity of unification of the internal chain, having technology of information, excellent communication among departments, providing training program for workers to increase its work abilities and multifunctional skills. To satisfy these requirements the author has been implementing some elements of the Just in time System/Lean to solve efficiently these issues by focusing on the cellular flow production design and the total kanban pull system, which will be supported by the Systematic Layout Planning (SLP). As the Just in Time is a very complex system to implement, these techniques will be considered as the first steps for the implementation of its elements in the factory. The most significant impact will be on the internal production process giving a competitive advantage in reducing some of its non-added-value such as lead times, material handling, inventories and distance traveling in order to respond rapidly to customer’s demand, with right quantity, at the right place, at the right time, at the right quality, and reduced costs of performance.